Hayabusa2 Thermal Infrared Imager (TIR) Bundle - Okada Tatsuaki; Tanaka Satoshi; Fukuhara Tetsuya; Arai Takehiko; Imamura Takeshi; Ogawa Yoshiko; Kitazato Kohei; Kouyama Toru; Sakatani Naoya; Shimaki Yuri; Sekiguchi Tomohiko; Senshu Hiroki; et al. (Institute of Space and Astronautical Science, Japan Aerospace Exploration Agency, 2021)
This PDS4 bundle collects all the operational data products produced by the Hayabusa2 TIR instrument.
Keywords: Hayabusa2; Spacecraft; (162173) Ryugu; Asteroid; Sample Return; Planetary Data System; PDS4; PDS4 Instrument Bundle; Thermal Infrared Imager; TIR